2020
DOI: 10.1155/2020/7239895
|View full text |Cite
|
Sign up to set email alerts
|

Mir-141-3p Regulates Apoptosis and Mitochondrial Membrane Potential via Targeting Sirtuin1 in a 1-Methyl-4-Phenylpyridinium in vitro Model of Parkinson’s Disease

Abstract: Objectives. Parkinson’s disease (PD) is a common neurodegenerative disease characterized by the loss of midbrain dopaminergic neurons in the substantia nigra. The present study investigated miR-141-3p/sirtuin1 (SIRT1) activity in a 1-methyl-4-phenylpyridinium- (MPP+-) induced PC12-cell model of PD. Methods. PC12 cells were exposed to MMP+ following induction of differentiation by nerve growth factor (NGF). miR-141-3p and SIRT1 expressions were examined using RT-qPCR and western blot. Cell viability was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
(16 reference statements)
1
22
0
Order By: Relevance
“…Further investigation confirmed the IL-1β-induced upregulation of miR-30d-5p and miR-141-3p in both ADEVs and astrocytes ( Gayen et al, 2020 ; Table 1 and Figures 1A,B ). Augmented miR-30d-5p has been shown to upregulate apoptosis and downregulate autophagy by respectively targeting SMAD2 ( Yu and Liu, 2020 ) and the autophagosome-associated protein Beclin 1 ( Zhao et al, 2017 ), while increased miR-141-3p, which downregulates the neuroprotective protein Sirtuin 1, was associated with increased apoptosis and mitochondrial dysfunction ( Zheng et al, 2020 ). Thus, similar effects could occur in both astrocytes and ADEV-ingesting cells ( Figures 1A,B ).…”
Section: Dysregulation Of Microrna and Their Target Mrna In Astrocyte...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation confirmed the IL-1β-induced upregulation of miR-30d-5p and miR-141-3p in both ADEVs and astrocytes ( Gayen et al, 2020 ; Table 1 and Figures 1A,B ). Augmented miR-30d-5p has been shown to upregulate apoptosis and downregulate autophagy by respectively targeting SMAD2 ( Yu and Liu, 2020 ) and the autophagosome-associated protein Beclin 1 ( Zhao et al, 2017 ), while increased miR-141-3p, which downregulates the neuroprotective protein Sirtuin 1, was associated with increased apoptosis and mitochondrial dysfunction ( Zheng et al, 2020 ). Thus, similar effects could occur in both astrocytes and ADEV-ingesting cells ( Figures 1A,B ).…”
Section: Dysregulation Of Microrna and Their Target Mrna In Astrocyte...mentioning
confidence: 99%
“…The neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and metabolite MPP+ are taken up into neurons via dopamine transporters, resulting in selective degeneration of dopaminergic neurons accompanied by parkinsonian symptoms ( Kitayama et al, 1998 ) and increased expression of α-syn protein in differentiated PC12 cells ( Zheng et al, 2020 ). Interestingly, exposure of astrocytes to MPP+ induces astrogliosis and the production of pro-inflammatory cytokines ( Yu et al, 2016 ) and alters the miRNA cargo of ADEVs ( Shakespear et al, 2020 ; Table 1 ).…”
Section: Dysregulation Of Microrna and Their Target Mrna In Astrocyte...mentioning
confidence: 99%
“…Both microRNA-141-3p (miR-141-3p) and microRNA-9-5p (miR-9-5p) were found to target the 3’ UTR of SIRT1 mRNA. Since SIRT1 inhibited the formation of α-syn aggregates, knockdown of miR-141-3p and miR-9-5p may alleviate oxidative stress and boost the viability of Das (Wang Z. et al, 2019 ; Zheng et al, 2020 ). In addition, microglia are thought to have a role in the pathophysiology of PD, since cytotoxic substances released from activated microglia can exacerbate oxidative stress.…”
Section: Interaction Between Oxidative Stress and Regulatory Ncrnas I...mentioning
confidence: 99%
“…Interestingly, Delavar et al [ 75 ] showed that miR-141 also targets SIRT1 expression and correlates with PD-related pathogenic processes. Mechanistically, in a 1-methyl-4-phenylpyridinium- (MPP+-) induced in vitro PD model, the upregulation of miR-141-3p induced increased apoptosis, oxidative stress, and mitochondrial membrane potential through the direct targeting of SIRT1 expression [ 69 ]. The same study also shows that resveratrol (a SIRT1 activator) blocked and sirtinol (a SIRT1 inhibitor) reversed the abovementioned biological effects of miR-141-3p, respectively.…”
Section: Mir-200 Family In Pathophysiologymentioning
confidence: 99%